Engagement of primary care physicians in medication decision-making for patients with multimorbidity in China: A cross-sectional study - Liyan Han; Leyi Jiang; Mi Yao; Yu Xia; Ming Yan; Junhai Zhen; Lingyan Wu; Yi Guo; Yuling Tong; Zhijie Xu (PLoS ONE, 2026)
Background Managing medications for patients with multimorbidity is complex and often leads to medication-related problems. Primary care physicians (PCPs) play a critical role in optimizing medication use but face considerable challenges and research on their practices remains limited. This study aimed to examine PCPs’ medication decision-making practices for patients with multimorbidity, identify associated factors, and explore perceived difficulties. Methods A cross-sectional survey was conducted among PCPs in five regions of Zhejiang, China, using a self-administered questionnaire. Descriptive statistics were used to assess PCPs’ engagement in medication decision-making and their perceived difficulties. Linear regression analyses were performed to identify factors associated with PCPs’ overall engagement of medication decision-making practices. Results A total of 346 valid responses were included in the final analysis. PCPs showed limited engagement in eliciting patient preferences and addressing individual concerns. Perceived difficulties included difficulties in understanding complex medication regimens and adverse reactions, evaluating overall benefits and risks, and discussing treatment alternatives. Linear regression analysis revealed that daily outpatient volume (B = −0.046, 95% CI: −0.083 to −0.008), prior training in medication use (B = 5.764, 95% CI: 1.559 to 9.969), and collaboration with pharmacists (B = 7.048, 95% CI: 3.313 to 10.782) were significantly associated with more appropriate decision-making practices. Conclusion While many PCPs reported general engagement in medication decision-making, gaps remain in managing complex therapies and delivering patient-centered care. Targeted pharmaceutical training and strengthened interprofessional collaboration may support PCPs in improving medication decisions for patients with multimorbidity.